Plasticity of Metallic Materials : Modeling and Applications to Forming - Cazacu, Oana, author 651702; Revil-Baudard, Benoit, author 651703; ScienceDirect (Online service) 7722 (Amsterdam : Elsevier, 2021)
Plasticity of Metallic Materials presents a rigorous framework for description of plasticity phenomena, classic and recent models for isotropic and anisotropic materials, new original analytical solutions to various elastic/plastic boundary value problems and new interpretations of mechanical data based on these recent models. The book covers models for metals with both cubic and hexagonal crystal structures, presents the mechanical tests required to determine the model parameters, various identification procedures, verification, and validation tests, and numerous applications to metal forming.